Current practices of virtual community and their influence of social cohesion - Md Dahalin, Zulkhairi; Yusop, Nor Iadah; Mat Aji, Zahurin; Ibrahim, Huda; Kasiran, Mohd Khairudin (2015)
This paper aims to determine whether social cohesion can be informed by current practices of virtual community members represented by four research variables namely experiences in using the social media, the types and preference of social media used, and their involvement in certain categories of virtual community.These four research variables were tested against the virtual community cohesion constructs to determine significant relationships and to predict their influence on social cohesion in the virtual community environment.Results of this study show that Experience, Types of Social Media and Virtual Community Involvement are current practices in the virtual community that can influence social cohesion.Social Media Preference was however not found to be significant in influencing social cohesion.